Anais Do Congresso Brasileiro De Engenharia Química Em Iniciação Científica - Cobeq IC 2015 2015
DOI: 10.5151/chemeng-cobeqic2015-162-32599-263646
|View full text |Cite
|
Sign up to set email alerts
|

Biossorção Do Corante Têxtil Azul 5g Utilizando O Bagaço De Malte

Abstract: RESUMO-O objetivo do trabalho é avaliar a aplicação do bagaço de malte como material adsorvente no processo de adsorção do corante comercial azul 5G. Nos experimentos investigou-se a influência do pré-tratamento químico do bagaço de malte na adsorção do corante e a influência da velocidade de agitação na cinética de adsorção. Em cada experimento, alíquotas foram retiradas e a concentração de corante em solução quantificada mediante a leitura da absorbância em espectrofotômetro. Os resultados obtidos demonstrar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
(1 reference statement)
1
1
0
1
Order By: Relevance
“…Throughout the biosorption, these sites are occupied by the dye, and consequently, the surface becomes saturated, which reflects on the decreased removal rate until equilibrium is reached (Cruz et al., 2004; Debrassi et al., 2011). Such behavior was also identified by other researchers who studied the biosorption of reactive dyes by malt bagasse, such as Zanette et al. (2015), Fontana et al.…”
Section: Resultssupporting
confidence: 70%
“…Throughout the biosorption, these sites are occupied by the dye, and consequently, the surface becomes saturated, which reflects on the decreased removal rate until equilibrium is reached (Cruz et al., 2004; Debrassi et al., 2011). Such behavior was also identified by other researchers who studied the biosorption of reactive dyes by malt bagasse, such as Zanette et al. (2015), Fontana et al.…”
Section: Resultssupporting
confidence: 70%
“…Estes corantes afetam a transparência da água mesmo em pequenas concentrações, são tóxicos e pouco biodegradáveis (CHEN et al, 2018). O processo de adsorção tem sido muito utilizado para o tratamento de efluentes por se tratar de um método simples, de baixo custo e alta eficiência, empregando diversos tipos de adsorventes e biossorventes -materiais de origem biológica capazes de adsorver poluentes (ZANETTE et al, 2015). O carvão ativado é o mais popular e eficiente adsorvente usado na remoção de cor para o tratamento de efluentes.…”
Section: Introductionunclassified
“…Thus, the drying of malte bagasse is the first step for the biomass preparation. Piffer et al [5] studied the adsorption of textile dye on malt bagasse in order to evaluate the efficiency of the process and Zanette et al [6] reported the adsorption of 5G blue dye using the malt bagasse, verifying the influence of the agitation speed in the process.…”
Section: Introductionmentioning
confidence: 99%